2017
DOI: 10.1128/aac.02277-16
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the DNA Gyrases in Fluoroquinolone-Resistant Mutants of Francisella novicida

Abstract: Fluoroquinolone (FQ) resistance is a major health concern in the treatment of tularemia. Because DNA gyrase has been described as the main target of these compounds, our aim was to clarify the contributions of both GyrA and GyrB mutations found in Francisella novicida clones highly resistant to FQs. Wild-type and mutated GyrA and GyrB subunits were overexpressed so that the in vitro FQ sensitivity of functional reconstituted complexes could be evaluated. The data obtained were compared to the MICs of FQs again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Whether the hypothetical link between fupA/B mutations and ciprofloxacin susceptibility [5] is another specific feature of the fusion gene, or whether it is inherited from fupA and/or fupB ancestors is currently unknown. In agreement with the latter hypothesis, we observed that a highly FQ-resistant mutant of F. novicida (U112_Fno3) bearing a functionally-inert DNA gyrase mutation (GyrA_ΔE524, ΔS525) also had a nonsense mutation in FTN_0444 ( fupA ) [7]. Moreover, fupA was identified as one of seven mutated genes in a ciprofloxacin-resistant mutant of F. tularensis SCHU S4, alongside gyrA and parE [14].…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Whether the hypothetical link between fupA/B mutations and ciprofloxacin susceptibility [5] is another specific feature of the fusion gene, or whether it is inherited from fupA and/or fupB ancestors is currently unknown. In agreement with the latter hypothesis, we observed that a highly FQ-resistant mutant of F. novicida (U112_Fno3) bearing a functionally-inert DNA gyrase mutation (GyrA_ΔE524, ΔS525) also had a nonsense mutation in FTN_0444 ( fupA ) [7]. Moreover, fupA was identified as one of seven mutated genes in a ciprofloxacin-resistant mutant of F. tularensis SCHU S4, alongside gyrA and parE [14].…”
Section: Introductionmentioning
confidence: 54%
“…The topic of antibiotic tolerance is complex, and the resistance of F. tularensis to FQ is definitely not solely a consequence of DNA gyrase mutations [5,7]. The work presented in this paper reveals a new pathway based on FupA/B or FupA alterations through which FQ could drive the emergence of drug resistance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The specific regions altered in Gyr A that give Francisella enhanced resistance are residues 83 and 87, which are involved in the catalytic domain, 43, 523, and 524 which are involved with DNA binding ( Figure 2A ). Those altered in GyrB are catalytic residues 464–466, DNA binding residues 486, 487, and 747, as well as mutation in residues 570 and 86, which have unknown roles in protein functionality ( Sutera et al, 2014b ; Caspar et al, 2017 ) ( Figure 2B ).…”
Section: Intrinsic Antibiotic Resistance In Francisellamentioning
confidence: 99%
“…Doxycycline is a second generation tetracycline that inhibits bacterial translation by reversible binding to the 30S ribosomal subunit (23,24). Ciprofloxacin is a quinolone that inhibits bacterial replication by binding to DNA gyrases and topoisomerase IV (25)(26)(27). The importance of the use of these two drugs in a mass casualty setting underscores the need to understand the efficacy of these drugs and the evolvability of resistance to this combination.…”
Section: Introductionmentioning
confidence: 99%